THE POLITICAL HISTORY IN THE BICENTENARY: BETWEEN THE HISTORY OF THE PRESENT AND THE CONCEPTUAL HISTORY. REFLECTIONS ABOUT THE NEW POLITICAL HISTORY. - Moyano Barahona, Cristina (Revista de Historia Social y de las Mentalidades, 2011)
Article that realizes an analytical reflexive  tour on the new courses of the political  contemporary history in Chile, specially those  innovative elements that have joined with the  development of the history of the present time  and of the conceptual history.
Keywords: Political history; conceptual history; contemporany history